Classical creativity: A functional magnetic resonance imaging (fMRI) investigation of pianist and improviser Gabriela Montero - Karen Chan Barrett; Frederick Streeter Barrett; Patpong Jiradejvong; Summer K. Rankin; Andrew T. Landau; Charles J. Limb (NeuroImage, 2020)
Improvisation is sometimes described as instant composition and offers a glimpse into real-time musical creativity. Over the last decade, researchers have built up our understanding of the core neural activity patterns associated with musical improvisation by investigating cohorts of professional musicians. However, since creative behavior calls on the unique individuality of an artist, averaging data across musicians may dilute important aspects of the creative process. By performing case study investigations of world-class artists, we may gain insight into their unique creative abilities and achieve a deeper understanding of the biological basis of musical creativity.In this experiment, functional magnetic resonance imaging and functional connectivity were used to study the neural correlates of improvisation in famed Classical music performer and improviser, Gabriela Montero. GM completed two control tasks of varying musical complexity; for the Scale condition she repeatedly played a chromatic scale and for the Memory condition she performed a given composition by memory. For the experimental improvisation condition, she performed improvisations. Thus, we were able to compare the neural activity that underlies a generative musical task like improvisation to 'rote' musical tasks of playing pre-learned and pre-memorized music. In GM, improvisation was largely associated with activation of auditory, frontal/cognitive, motor, parietal, occipital, and limbic areas, suggesting that improvisation is a multimodal activity for her. Functional connectivity analysis suggests that the visual network, default mode network, and subcortical networks are involved in improvisation as well. While these findings should not be generalized to other samples or populations, results here shed insight into the brain activity that underlies GM’s unique abilities to perform Classical-style musical improvisations.